SERS platforms of plasmonic hydrophobic surfaces for analyte concentration: Hierarchically assembled gold nanorods on anodized aluminum - Tebbe, Moritz; Cherepanov, Pavel; Skorb, Ekaterina V.; Poznyak, Sergey K.; Garcia De Abajo, Javier; Fery, Andreas; Andreeva, Daria V.; Alvarez Puebla, Ramon A.; Pazos-Perez, Nicolas (Particle & Particle Systems Characterization, 2014)
Effi cient and homogeneous surface-enhanced Raman scattering (SERS) substrates are usually prepared using lithographic approaches, physical evaporation, or in situ chemical reduction. However, these approaches are time-consuming, expensive, and very diffi cult to upscale. Alternatively, template- assisted approaches using colloidal suspensions of preformed nanoparticles have become more popular because of their low cost, fast production, and ability to be scaled up easily. One of the limitations of these methods is the dimensions of the structured surfaces. In this context, a new method for designing low-cost, up-scalable surface patterns that match building block dimensionality based on anodization of aluminum, enabling a hierarchical organization of anisotropic nanoparticles, is presented. The proposed new technology starts with anodized aluminum oxide with regular parallel linear periodicities. To produce a highly effi cient plasmonic surface, gold nanorods are assembled into parallel lines where the long axes of the Au rods are also oriented along the substrate lines, thus inducing reproducible tip-to-tip plasmonic coupling with the corresponding generation of highly active hotspots. Additionally, this advanced material presents an inherent hydrophobicity that can be exploited as a method for concentration of analytes on the surface. SERS detection is demonstrated with benzenethiol and 2-naphtoic acid.
CRIS-Team Scopus Importer:2023-03-20